A Comparison of Vietnamese and Korean Organzational Communication - Nguyễn, Thị Vân Hạnh (H. : ĐHQGHN, 2017)
Communication is central to the life of our culture. Within communication theory, scientists often study the interaction of people from different cultures. The study of communication involves the study of culture with which it is integrated. This paper discusses on the differences of communication in Korean and Vietnamese organizations.